Betonan and Paroan: Local Wisdom in Traditional Bondowoso Agriculture as An Implementation of Islamic Economic Fiqh - Ubaidillah, Ubaidillah; Munir, Muhammad Sirajul; SAM, Achmad Al-Muhajir; Hanip, Abdul (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2025)
Betonan and Paraon is a local wisdom practice that developed in the traditional agricultural system of the Bondowoso people. Both not only reflect patterns of cooperation and social solidarity, but also contain values ​​that align with the principles of Islamic economic jurisprudence, particularly regarding justice and mutual assistance (the plague), and proportional distribution of results. This research aims to explore the meaning, mechanisms, and relevance of the tradition betonan and paroan from the perspective of Islamic economic jurisprudence. By using a descriptive qualitative approach through literature studies and interviews, researchers found that the practice betonan which is based on cooperation and paroan which emphasizes fair distribution of profits, reflecting sharia principles such as muzara'ah And mukhabarah The implementation of this local wisdom not only strengthens the economic resilience of the Bondowoso farming community but also represents a concrete form of integration between cultural traditions and Islamic values. Thus, betonan and paroan can be seen as a sharia-based economic practice that grows from local cultural roots and is relevant to be developed in contemporary Islamic economic discourse.